Effectiveness of Video-Based Instruction, Teachers’ Performance and Challenges among Junior High School Teachers in the New Normal in the District of Masinloc, Division of Zambales - Shirley H. Fabunan, MAEd-EA; Emma C. Ventura, Ed.D (Researchparks Publishing, 2021)
The video-based instruction (VBI) was used as alternative classroom teaching and learning instruction and observation processes which is common in today’s educational venues in the new normal of education. However, there has been a dearth of awareness and training to help teachers critically analyze and effectively utilize video-based instruction of authentic classroom instruction for their technological and pedagogical development. The study aimed to evaluate the effectiveness of video-based instruction as a teaching approach and its relation to the teacher performance and challenges among Junior High School Teachers in the New Normal situation in the district of Masinloc, Division of Zambales during the School Year 2020-2021.